2021
DOI: 10.1002/ijop.12825
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of the relation between academic stress and anxiety symptoms among adolescents in India: The role of physiological hyperarousal and social acceptance

Abstract: Academic stress is a critical aspect of adolescent experience around the world, but particularly in countries with dense populations that lead to highly competitive college admissions. With a population of over one billion people, the competition for higher education in India is significantly high. Although research has shown that academic pressures are associated with anxiety in adolescents, this work is primarily cross‐sectional. The current study examined academic stress and anxiety symptoms over time and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This study provides evidence that a higher level of academic pressure was positively associated with anxiety symptoms among adolescents, even after adjusting for age, sex, BMI, cortisol, living arrangement, classmate relations, and teacher-classmate relations. Similarly, Zhu et al found a positive correlation between academic pressure and anxiety symptoms among Chinese adolescents [ 16 ], Karki et al reported a significant association between perceived academic pressure and anxiety symptoms among high school students in Nepal [ 42 ], and Trevethan et al observed a longitudinal direct effect of academic pressure on changes in symptoms of generalized anxiety and panic [ 43 ]. According to Lazarus’s cognitive appraisal theory, stress is seen as a relation between individuals and their environment [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study provides evidence that a higher level of academic pressure was positively associated with anxiety symptoms among adolescents, even after adjusting for age, sex, BMI, cortisol, living arrangement, classmate relations, and teacher-classmate relations. Similarly, Zhu et al found a positive correlation between academic pressure and anxiety symptoms among Chinese adolescents [ 16 ], Karki et al reported a significant association between perceived academic pressure and anxiety symptoms among high school students in Nepal [ 42 ], and Trevethan et al observed a longitudinal direct effect of academic pressure on changes in symptoms of generalized anxiety and panic [ 43 ]. According to Lazarus’s cognitive appraisal theory, stress is seen as a relation between individuals and their environment [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, adolescents in Nepal facing academic stress are 2.4 times more likely to develop depression compared to their peers without such pressures [14]. A study in India found that academic stress had direct impact on changes in symptoms of generalized anxiety and panic among adolescents [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, anxiety as a physiological and psychological response triggered by stressors ( Colich and McLaughlin, 2022 ), and stressful life events are a major stressor ( Young and Dietrich, 2015 ). The higher the academic stress of adolescents, the higher their anxiety levels ( Leung et al, 2010 ; Trevethan et al, 2022 ). Empirical studies have shown that adolescents increase academic stress ( Park et al, 2012 ; Sun et al, 2012 ) and thus anxiety levels ( Huberty, 2009 ) due to high homework loads, high expectations of teachers and parents, and lower academic performance.…”
Section: Introductionmentioning
confidence: 99%